2022
DOI: 10.1007/s11071-022-07223-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic analysis of variable lead preloaded single nut ball screw considering the variation of working parameters

Abstract: In this study, a 5-degrees-of-freedom dynamic model of variable lead preloaded single nut ball screw is proposed. The proposed model considers the effect of excitation amplitude, deflection angle, the number of balls, and the preload into consideration. Moreover, to study the effect of working parameters on nonlinear dynamics, bifurcation diagram, 3-D frequency spectrum, phase diagram and Poincaré section with different system parameters are shown in discussion section. The numerical analysis indicates that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In equation ( 6), K h denotes the Hertz contact stiffness between the ball and the raceway in the ball screw pair, which is related to the geometric parameters of the ball screw pair and the characteristic parameters of the material. Because the initial displacement of the ball screw pair is relatively small when subjected to axial load, the axial nonlinear elastic recovery force 8 generated by the ball screw pair in Figure 2 is:…”
Section: Elastic Recovery Force Of Ball Screw Pairmentioning
confidence: 99%
See 1 more Smart Citation
“…In equation ( 6), K h denotes the Hertz contact stiffness between the ball and the raceway in the ball screw pair, which is related to the geometric parameters of the ball screw pair and the characteristic parameters of the material. Because the initial displacement of the ball screw pair is relatively small when subjected to axial load, the axial nonlinear elastic recovery force 8 generated by the ball screw pair in Figure 2 is:…”
Section: Elastic Recovery Force Of Ball Screw Pairmentioning
confidence: 99%
“…Zhou et al 7 proposed a new load distribution model, and the critical axial load of a double nut ball screw pair with additional elastic elements can be obtained. Liu et al 8 proposed a five-degree-of-freedom dynamic model for a variable lead preloaded single nut ball screw feed system. The model considers the effects of excitation amplitude, deflection angle, number of balls, and preload.…”
Section: Introductionmentioning
confidence: 99%
“…These studies underscore the significant impact of nonlinear joint characteristics and thermal effects on the dynamic behavior and machining accuracy. Liu et al [80] focus on the nonlinear dynamic analysis of a variable lead preloaded single nut ball screw, considering the variation of working parameters. This research highlights the sensitivity of dynamic behavior to operational and design parameters, guiding the development of more robust and adaptable screw mechanisms.…”
Section: Nonlinear Dynamicsmentioning
confidence: 99%
“…Step 3: Calculate the actual contact area and the force Three different deformation states of the asperities are analyzed and the critical contact areas are obtained by the Eqs. ( 12) and (13). Then the contact force is obtained by the Eqs.…”
Section: Transmission Efficiency Of the Ball Screwmentioning
confidence: 99%
“…He concluded that the preload can increase the nonlinear properties of the whole ball screw system. 13 Zhao studied the relationship between the wear and the preload degradation to estimate the position accuracy of the ball screw. It proves that the preload is linear with the wear depth and the higher the rotational speed is, the more precision lose.…”
Section: Introductionmentioning
confidence: 99%